The Kinerja Guru Madrasah Inklusif: Mengkaji Pengaruh Efikasi Diri dan Persepsi Guru terhadap Kompetensi Kepala Madrasah dengan Kepuasan Kerja sebagai Mediator: Kinerja Guru Madrasah Inklusif: Mengkaji Pengaruh Efikasi Diri dan Persepsi Guru terhadap Kompetensi Kepala Madrasah dengan Kepuasan Kerja sebagai Mediator - Eva Sri Wahyuni; Achmad Syahid (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
This study aims to examine the theoritical model of the effect of teacher self-efficacy and teacher perceptions of the competence of Madrasah Principals on the performance of Inclusive Madrasah teachers with job satisfaction as a mediator. The population in this study were teachers of Madrasah Aliyah (MA), Madrasah Tsanawiyah (MTs), Madrasah Ibtidaiyah (MI) and Raudhatul Athfal (RA) both public and private in the Java Island region which again amounted to 2,184 people. The sampling technique used is purposive sampling which is a type of non-probability sampling, 358 respondents who participated, only 19 had to be dropped because they did not meet the research criteria, so that the total respondents analyzed were 339 people. The measuring instruments used in this study include Teacher Performance Assessment (PKG), Madrasah Principal Competency Instruments, Norwegian Teacher Self-Efficacy Scale (NTSES) and The Teacher Job Satisfaction Scale (TJJS-9). Data analysis using Structural Equating Modeling (SEM) with Lisrel 8.8 software. The results of the Structural Equating Modeling (SEM) analysis found that the theoretical model of the influence of self-efficacy and teacher perceptions of the competence of the madrasah principal on the performance of Madrasah Inclusion teachers with job satisfaction as a mediator fit with empirical data. The results showed that only the personality and managerial competence of the Madrasah Principal had a direct effect on teacher satisfaction and performance and an indirect effect on teacher performance through job satisfaction, apart from the three dimensions of teacher self-efficacy did not affect teacher performance directly through job satisfaction. Keywords: teacher performance, self-efficacy, competency of inclusive Madrasah Principals, quality of Indonesian madrasas, job satisfaction